STUDI KOMPARASI PENGGUNAAN TIPE STAD DENGAN JIGSAW TERHADAP HASIL BELAJAR IPA DI SEKOLAH DASAR - Jumatika, Jumatika; Kresnadi, Hery; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study is whether there are differences in student learning outcomes using STAD type cooperative models with Jigsaw in science V grade V Elementary School 05 East Pontianak. This study aims to analyze how much different learning outcomes of students who use STAD type with Jigsaw in science V grade V Elementary School 05 East Pontianak.This study uses an experimental method with the type of Quasi Experimental type nonequivalent Control group Design. The population is all fifth grade students of East Pontianak Public Elementary School 05 which consists of 115 students, sampling is nonprobability sampling purposive sampling type that is class VA and VB. Techniques used in data collection are direct observation and measurement with data collection tools used are objective written tests. Based on the data analysis, the results of the average VA class post-test 81.23 and the average post-test results of the VB students were 81.45. After t test is obtained, t-count is 0.146 while t table with db = 43 and significant level (Î±) = 5% is 1.9998, it turns out that t count <ttable or -0.146 <1.9998 which means there is no significant difference between science learning who uses the STAD type with the jigsaw type in class V Elementary School 05 pontianak Timur.Key words : Comparative Study, Type STAD, Type of Jigsaw, Learning Outcomes,Â Science